Assessment of the Needs of Complex Trauma-Exposed Boys and Girls in the Child Welfare System: Symptom Profile, Gender Differences, and Placement Disruption - Hopton, Jennifer (Université d'Ottawa / University of Ottawa, 2016)
This dissertation consists of two studies designed to broaden our understanding of the impact of complex trauma on symptom profiles and outcomes of children in the child welfare system through the lenses of gender, development, and placement permanency. Data for both were obtained using the Child and Adolescent Strengths and Needs Comprehensive Assessment tool (CANS; Lyons, Gawron, & Kisiel, 2005) for youth ages 6 -17 years involved in the child welfare system. In Study 1, I examined symptom profiles of 3,446 youth to determine the ability of gender, age, ethnicity, trauma type, and other adversity variables to predict the following CANS domains: posttraumatic stress symptoms (PTSS), emotional/ behavioral needs, risk behaviors, life domain functioning, and child strengths. Findings supported the hypothesis that males and females would exhibit a similar number and severity of PTSS subsequent to exposure to maltreatment, including complex trauma. Unique gender-specific developmental profiles of trauma exposure and symptomatology emerged. I concluded that the complex and dynamic interactions among gender, age, trauma experience, and psychosocial functioning are more complicated than can be elucidated in main effect or two-way interactions. It is therefore recommended that trauma researchers disaggregate analyses by gender in trauma research because the dynamics of trauma are different for males and females. In Study 2, I employed survival analyses to examine the ability of child characteristics, complex trauma exposure, and placement-related variables to predict placement disruption in a sample of 4,822 youth at high-risk for placement disruption. Older age, female gender, higher levels of externalizing behavior, and more prior placements increased risk for placement disruption, whereas longer time in care and type of out-of-home placement decreased risk for placement disruption in the sample. It is recommended that placement stability be directly targeted for those at higher risk through provision of intensive support to youth and their foster caregivers. Caseworkers should receive training about those subgroups most at-risk for placement disruption. Externalizing behavior and attachment, but not PTSS, mediated the relation between complex trauma and placement disruption. Intervention for youth with a history of complex trauma should focus on both attachment and externalizing behaviors.
Keywords: complex trauma; developmental trauma; Posttraumatic stress; child welfare; gender; youth; placement disruption; externalizing behavior; attachment